Kampf um die Weltmacht: die USA und das Dritte Reich 1933 - 1945 - Junker, Detlef (Historisches Seminar, 1988)
Literaturverz.SA ; Geschichte 1933-1945
Text teilw dt., teilw. engl
Keywords: Geschichte 1933-1945; United States -- Foreign relations -- Germany; Germany -- Foreign relations -- United States; Germany -- Foreign relations -- 1933-1945; United States -- Foreign relations -- 1933-1945; Germany -- Politics and government -- 1933-1945; United States -- Foreign relations -- Germany -- Sources; Germany -- Foreign relations -- United States -- Sources; Germany -- Foreign relations -- 1933-1945 -- Sources; United States -- Foreign relations -- 1933-1945 -- Sources; Germany -- Politics and government -- 1933-1945 -- Sources; USA; Deutschland; Quelle